1993
DOI: 10.1007/bf00040620
|View full text |Cite
|
Sign up to set email alerts
|

Studies of pollen grain germination, pollen tube growth, micropylar penetration and seed set in intraspecific and intergeneric crosses within three Cruciferae species

Abstract: Pollen grain germination, pollen tube growth and micropylar penetration were investigated in intraspecific and intergeneric crosses involving Brassica napus L. ssp. oleifera (Metzg.) Sinsk. (oil-seed rape or fodder rape), xBrassicoraphanus Sageret (Raparadish) and diploid (2x) and tetraploid (4x) accessions of Sinapis alba L. (white mustard). For the reciprocal intergeneric crosses between B. napus and xBrassicoraphanus no effective barriers to pollen tube growth on stigmata or in styles were observed. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In the present study, the percentage of pollen germination in all the crosses was significantly lower than the selfing of corresponding female parent at same time interval after pollination. This is similar to the results obtained by Lelivelt (1993) in intergeneric crosses between B. napus and S. alba (2x) and by Ramesh et al, (2003) in interspecific crosses of sesame. This shows that for pollen germination on stigma, proper recognition substances are necessary which might be lacking to promote pollen germination in interspecific crosses.…”
Section: With E-8supporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the percentage of pollen germination in all the crosses was significantly lower than the selfing of corresponding female parent at same time interval after pollination. This is similar to the results obtained by Lelivelt (1993) in intergeneric crosses between B. napus and S. alba (2x) and by Ramesh et al, (2003) in interspecific crosses of sesame. This shows that for pollen germination on stigma, proper recognition substances are necessary which might be lacking to promote pollen germination in interspecific crosses.…”
Section: With E-8supporting
confidence: 92%
“…However, reports of Lelivelt (1993) and Ramesh et al, (2003) indicated nonsignificant differences between control and interspecific crosses in B. napus x S. alba and S. occidentale x S. indicum, respectively.…”
Section: With E-8mentioning
confidence: 90%
“…The maternal parent seemed to play an important part in the degree of incompatibility, especially in the crosses using P. coccineus as the female parent. The maternal link to cross-compatibility has also been reported in the other interspecific crossing (Lelivelt 1993). More recently, Garcia et al (2005), FitzGerald et al (2008), and Hoe Huh et al (2008 have all supported the hypothesis that the maternal genome plays the predominant role in controlling early seed development.…”
Section: Discussionmentioning
confidence: 80%
“…Matromorphy (production of progeny that are genetically identical to the female parent) is a common phenomenon in interspecific crosses (Ayotte et al, 1988;Lelivelt, 1993). Matromorphs are thought to develop following micropylar penetration by the pollen tube and deposition of the male gamete in the embryo sac, followed by a parthenogenetic outgrowth of the unreduced egg cell without fertilization and subsequent elimination of the male gamete (Noguchi, 1928).…”
Section: True Hybrids and Matromorphsmentioning
confidence: 99%